Implementation Of Independent Curriculum Development In Islamic Cultural History Subjects At Islamic Boarding School-Based Islamic Senior High Schools (Study At Islamic Boarding School Development Madrasah Aliyah Majenang) - Mochammad Muntaha Dwi Yulianto; Muh Wasith Achadi (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to describe the implementation of the independent curriculum in the subject of Islamic Cultural History at Madrasah Aliyah Islamic Boarding School Pembangunan Majenang. The type of research used is field research or field research studies, namely directly to the field to obtain data. Majenang. The result of this study is that the implementation of the independent curriculum at MA PP Majenang refers to regulations from the Ministry of Religion, namely KMA 347 of 2022 concerning guidelines for the implementation of the independent curriculum in madrasas. Learning planning at MA PP Majenang starts from the preparation of the teacher first and of course also the management of the madrasah, then the terms KI (Core Competencies) and KD (Basic Competencies) in the 2013 curriculum are replaced with CP (Learning Outcomes), the syllabus is changed to the term KKTP (Criteria for Achievement of Learning Objectives), and the RPP (Learning Implementation Series) is changed to Teaching Modules. In its implementation, teachers give students the freedom to choose the material in the subject according to what they like and are interested in by of course spurring the learning goals that have been set which make learning more flexible. At the SKI evaluation stage, teachers need to develop teacher competencies in a sustainable manner both through teacher creativity and debriefing teachers.